POLICY VALUES ASURANSI JOINT LIFE SUAMI ISTRI DENGAN METODE PROSPEKTIF - NUGRAHA, I WAYAN SANDY BAYU; JAYANEGARA, KETUT; WIDANA, I NYOMAN (E-Jurnal Matematika; Vol 8 No 2 (2019), 2019)
Policy values are funds be held by insurance company that will be used for unexpected claims from insurance participants. The purpose of this work is to calculate constant annual premiums with and without pure endowment on joint life couple insurance, then determine and calculate formula policy values with prospective method. The policy values ?? in joint life couple insurance, are affected by premium payments. Policy values ?? benefit at the end of the 1st year until the end of the 11th year will increase, because the money received by insurance company from premium payments is more than the sum insured to be paid. Policy values ?? benefit at the end of the 11th year until the end of the 66th year will decrease because there are no more premium payments.